2000
DOI: 10.1034/j.1398-9995.2000.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarush SIT in venom allergy

Abstract: 4. SIRAGANIAN RP. Automated histamine analysis for in vitro allergy testing. II. Correlation of skin test results with in vitro whole blood histamine release in 82 patients. J Allergy Clin Immunol 1977;59:214. 5. LEBEL B, MESSAAD D, SAHLA H, et al. Usefulness of histamine release for the diagnosis of drug allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…[ 209 ] At the injection site, the immunotherapy of allergies that included alum (aluminum hydroxide) as an adjuvant exhibited a number of adverse effects, such as puffiness, cutaneous nodules, indurations, inflammation, and granulomas. [ 210 ] In an effort to bypass this challenge, scientists have seen the possibility of using polymeric NPs [ 211 ] and agents that target toll‐like receptors (TLR) as alternate adjuvants. [ 212 ] An example of an adjuvant would be protamine‐based NPs containing TLR‐9 ligand cytosine phosphate guanine (CpG)‐oligodeoxynucleotides (ODNs).…”
Section: Nanotechnology In Protection Of Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 209 ] At the injection site, the immunotherapy of allergies that included alum (aluminum hydroxide) as an adjuvant exhibited a number of adverse effects, such as puffiness, cutaneous nodules, indurations, inflammation, and granulomas. [ 210 ] In an effort to bypass this challenge, scientists have seen the possibility of using polymeric NPs [ 211 ] and agents that target toll‐like receptors (TLR) as alternate adjuvants. [ 212 ] An example of an adjuvant would be protamine‐based NPs containing TLR‐9 ligand cytosine phosphate guanine (CpG)‐oligodeoxynucleotides (ODNs).…”
Section: Nanotechnology In Protection Of Foodmentioning
confidence: 99%
“…[ 207 , 208 ] Despite these attempts, several nanomaterials have been shown to induce allergic pulmonary inflammation in human beings. [ 209 , 210 ] For example, it has been shown that allergen‐specific immune responses of the Th2‐type may be induced in vivo by female BALB/c mice exposed to SiO 2 nanoparticles. [ 209 ] At the injection site, the immunotherapy of allergies that included alum (aluminum hydroxide) as an adjuvant exhibited a number of adverse effects, such as puffiness, cutaneous nodules, indurations, inflammation, and granulomas.…”
Section: Nanotechnology In Protection Of Foodmentioning
confidence: 99%